MEKANISME PELAKSANAAN PEMBERIAN IZIN USAHA SEKTOR PERTANIAN DI KABUPATEN ACEH BARAT DAYA - Shela Rahmadani; Basri Basri (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
The legal basis for business licensing in the agricultural sector is based on PP Number 24 of 2018 concerning electronically integrated business licensing services. As for getting this business license, business actors can register it through OSS (online single submission) where business actors are assisted by office employees where they take care of the licensing process. The purpose of the study was to find out the mechanism for granting business permits in the agricultural sector and to find out the obstacles faced by entrepreneurs in administering business permits for the Agricultural Sector at the Office of the Investment and One Stop Service, Manpower and Transmigration Office, Southwest Aceh Regency. The method used in this study is empirical law that uses descriptive research methods, in which this study describes the application of business licensing in the agricultural sector based on a review of state administrative law at the Office of Investment and One Stop Integrated Services, Manpower and Transmigration, Aceh Barat Daya Regency. The results of the study indicate that the mechanism for granting agricultural business permits at the Office of Investment and One-Stop Integrated Services, Manpower and Transmigration in Southwest Aceh Regency, namely: The applicant comes to the Office to collect the application form, The service counter officer checks the application file and administrative requirements for licensing and it is stated that the file is complete and correct, a receipt for the application file is made to the applicant, The service officer records the applicant's data and attaches a control form to the application file. Obstacles in obtaining business permits for the agricultural sector in Aceh Barat Daya Regency are: There are still limited human resources and there are still many people who still do not understand how to register online. There is still a lack of facilities and infrastructure. There are not enough human resources within the scope of the Southwest Aceh one-stop service office.